Effect of Wastewater Discharge of Aquaculture and ItsPrevention &Treatment Suggestion in China - WANG Chengcheng; JIAO Cong; SHEN Zhenyao; CHEN Lei (Renmin Zhujiang)
Aquaculture is easily to cause eutrophication and antibiotic pollution in water.However, there is currently no systematic study on the impact of aquaculture wastewater dischargeon the surrounding environment in China. This paper systematically introduces the causes ofeutrophication and antibiotic pollution in aquaculture and the eco-environmental risk ofwastewater discharge on surrounding water through literature review and data analysis, and putsforward the suggestions on prevention & treatment of wastewater discharge of aquaculture from fouraspects such as technical methods, aquaculture models, management methods and policies.